Game ‘I Know My Body’ Application to Encourage English Learning Process in Kindergarten - Nur Lailatul Aqromi; Dwija Wisnu Brata; Achmad Nurchoelis (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2017)
Learning in early childhood requires special understanding due to the character of children who are easily bored; particularly in case of English learning process that is not their mother tongue. One of children’s character is that they love all forms of games, so the game could be considered as one way to attract the their curiousity. Thus, game can be used as a medium for young learner especially in kindergarten to learn English. This paper provides an elaboration how to use a game to improve English learning process for young learner. The method of this study used Classroom Action Research. The game is Java-based and the content of the game is based on kindergarten curriculum that contains of some important basic aspects covered by English Language development aspect for kindergarten. To sum up, through game, the students of kindergarten feel fun and challenging to fulfill the the game, and in other side unconsciously they have learned English as well.